Simple reaction time in soccer players from differing categories and field positions Tempo de reação simples de jogadores de futebol de diferentes categorias e posições - Ruschel C.* (2011)
This study aimed at analyzing the visual and auditory simple reaction times in soccer players from differing categories and field positions. Participated in the study 49 male soccer players, amateurs and professionals, occupying the field positions of goalkeeper, center defender, right and left defender, half-back, midfielder, and forward. Data collection was carried out through a system composed by a switch, a mechanism of visual and auditory stimuli and appropriate acquisition software. Data were analyzed through descriptive and inferential statistics (p < .05). When comparing categories, there was no difference in visual reaction time (VRT). Professionals showed faster auditory reaction times (ART) than amateurs did. Regarding field positions, goalkeepers showed significantly faster VRT than midfielders and there was no difference in terms of ART. Main differences between players from differing categories and field positions may be due to the adoption of more complex strategies in retaining and using visual information in specific situations. ART may be less important in soccer, since this is essentially a visual game. © FTCD/CIDESD.